Development of Bilingual Mathematics Questions Based on Sidoarjo Local Wisdom for Two-Variable Linear Equation Systems - Nur Atiqoh, Ustadzah; Ayuningtyas, Nurina; Widadah, Soffil (Faculty of Teacher Training and Education, 2025)
This development research aims to produce bilingual mathematics questions on the topic of a Two-Variable Linear Equation System based on the local wisdom of Sidoarjo, Indonesia. The study employed the 4-D development model, encompassing the stages of Define, Design, Develop, and Disseminate. The study was conducted at Ten November Junior High School of Sidoarjo, a school with a bilingual program. The subjects for the product trial were 25 ninth-grade students. The primary outcome is a set of five bilingual test questions. The results demonstrate that the developed questions are highly valid based on expert judgment using the Content Validity Index (CVI) and empirical validity tests using Pearson Product-Moment correlation, where the r-count for all items exceeded the r-table (0.396) with a significance value of p < 0.05. The reliability test, measured by Cronbach's Alpha, yielded a score of 0.855, indicating high internal consistency. Furthermore, the questions proved effective, as evidenced by the majority of students achieving the minimum mastery criteria and their positive questionnaire responses regarding the questions' readability, benefits, and appeal. In conclusion, the bilingual mathematics questions based on Sidoarjo's local wisdom are valid, reliable, and effective, making them a suitable instrument for evaluation and a potential alternative learning resource.